The Influence of Organizational Culture, Work Motivation, Transformational Leadership on Employee Performance and the Implication on Organizational Performance - Nurmilasari Evi; Yuliantini Tine (Journal Research of Social Science, Economics, and Management, 2022)
The purpose of this study was to identify and determine the effect of Organizational Culture (OC), Work Motivation (WM) and Transformational Leadership (TL) on Employee Performance (EP) and the implication on Organizational Performance (OP) in National Research and Innovation Agency. The research was conducted through the distribution of questionnaires, and the population of this study were employees of the National Research and Development Agency. That was done to 179 respondents using a quantitative approach. The approach used in this research is Structural Equation Model (SEM) based on variant or Partial Least Square (PLS) with Smart-PLS analysis tools 3.3.9. The results of this study are that Organizational Culture, Work Motivation has a significant positive effect on Employee Performance and Organizational Performance. Transformational Leadership has a significant negative effect on Employee Performance and Organizational Performance. Employee Performance has a significant positive effect on Organizational Performance.